2017
DOI: 10.1553/populationyearbook2016s187
|View full text |Cite
|
Sign up to set email alerts
|

Subjective survival expectations and observed survival: How consistent are they?

Abstract: In this paper, we use new models to convert subjective expectations elicited from individual responses into conditional survival functions. We also estimate the effects of individual characteristics and assess the impact of health shocks on individual updates of subjective expectations. We use Health and Retirement Study (HRS) data from 1992 to 2006. By and large, our results confirm past empirical findings, but also identify patterns not documented in previous research. We show that the subjective probabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…This has been done in Aktas and Sanderson (2015), in which estimates from anticipated life tables were transformed into anticipatory ages. Palloni and Novak (2017) showed that subjective life tables and observed life tables are consistent with each other.…”
Section: Anticipated Longevitysupporting
confidence: 66%
“…This has been done in Aktas and Sanderson (2015), in which estimates from anticipated life tables were transformed into anticipatory ages. Palloni and Novak (2017) showed that subjective life tables and observed life tables are consistent with each other.…”
Section: Anticipated Longevitysupporting
confidence: 66%
“…The latter is consistent with past literature showing that African-Americans in the US tend to overestimate their survival chances in later life (e.g., RoebuckBulanda et al 2009;Hurd & McGarry 1995;Irby-Shasanmi 2013;Mirowsky 1999;Palloni & Novak 2016;and Hurwitz et al 2022b). 10 E.g., Pieters 2004, 2007;Muermann et al 2006;and George & Dane 2016. …”
supporting
confidence: 92%
“…See for instance RoebuckBulanda et al 2009;Hurd & McGarry 1995;Irby-Shasanmi 2013;Mirowsky 1999;Palloni &Novak 2016: andHurwitz et al 2022b. …”
mentioning
confidence: 99%
“…Rational expectations models (e.g., rational addiction models) are grounded on the assumption that individuals accurately form their survival expectations (Yaari, 1965). Consistently, some research has documented that subjective survival expectations are on average consistent with life table probabilities (Hurd & McGarry, 1995;Hurd & McGarry, 2002;Palloni & Novak, 2016). However, more recent studies show that aggregate life table realizations do not account for individual-specific heterogeneity (Gan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2 Some datasets, such as the Health and Retirement Survey (HRS) in the United States and the Survey of Health Ageing and Retirement in Europe (SHARE) contain a specific module with an end-of-life panel component which exhibits to date a reasonable sample and response rate. Some studies have already documented evidence of an age specific distribution of subjective and objective survival in the United States (Bissonnette et al, 2017;Palloni & Novak, 2016). 3 Alternatively, behavioural biases such as longevity optimism, or the individual specific tendency to view the future more in one's favour, can underpin individuals' differences in survival expectations.…”
Section: Introductionmentioning
confidence: 99%